Taxonomy and faunistics of the southern African genus Iselma, with the description of nine new species (Coleoptera: Meloidae: Eleticinae) - Pitzalis, Monica; Bologna, Marco A. (Zootaxa, 2008)
The genus Iselma belongs to the most basal subfamily Eleticinae and it is strictly distributed in the western portion of southern Africa. The taxonomy of this group was previously treated, but it is still incomplete and unclear. In this contribution we clarified some taxonomic misinterpretations and we describe nine new species: I. audisioi sp. n., I. cedarbergensis sp. n., I. elephantula sp. n., I. fontisamarae sp. n., I. kamanjabi sp. n., I. kaszabi sp. n., I. lorenzettii sp. n., I. mimica sp. n., I. stellaris sp. n.. The following new synonymies are proposed: I. analis Kaszab, 1953 = I. simillima Kaszab, 1953; I. hirsuta (Thunberg, 1791) = I. ursus (Thunberg, 1791). This taxonomic improvement required the proposal of a new updated key to the species. New faunistic records for several species are also included, and the phenomenon of extreme endemicity in this genus is highlighted.